Holistic Photoprotection, Broad Spectrum (UVA-UVB), and Biological Effective Protection Factors (BEPFs) from Baccharis antioquensis Hydrolysates Polyphenols - Monsalve-Bustamante, Yéssica A; López-Figueroa, Félix; Vega Sánchez, Julia; Rodrigues Moreira, Bruna; Puertas-Mejía, Miguel; Mejía-Giraldo, Juan C. (MDPI, 2023)
Overexposure to solar radiation has become an increasingly worrying problem due to the damage to the skin caused by ultraviolet radiation (UVR). In previous studies, the potential of an extract enriched with glycosylated flavonoids from the endemic Colombian high-mountain plant Baccharis antioquensis as a photoprotector and antioxidant was demonstrated. Therefore, in this work we sought to develop a dermocosmetic formulation with broad-spectrum photoprotection from the hydrolysates and purified polyphenols obtained from this species. Hence, the extraction of its polyphenols with different solvents was evaluated, followed by hydrolysis and purification, in addition to the characterization of its main compounds by HPLC–DAD and HPLC–MS, and evaluation of its photoprotective capacity through the measurement of the Sun Protection Factor (SPF), UVA Protection Factor (UVAPF), other Biological Effective Protection Factors (BEPFs), and its safety through the cytotoxicity. In the dry methanolic extract (DME) and purified methanolic extract (PME), flavonoids such as quercetin and kaempferol were found, which demonstrated antiradical capacity, as well as UVA–UVB photoprotection and prevention of harmful biological effects, such as elastosis, photoaging, immunosuppression, DNA damage, among others, which demonstrates the potential of the ingredients in this type of extract to be applied in photoprotection dermocosmetics.
Keywords: Piel -- Efectos de la radiación -- Protección; Rayos ultravioletas -- Protección; Radiación solar -- Protección; Baccharis antioquensis; Dermocosmetic; Natural sunscreen; Photoprotection; UVA–UVB